Paradigm and pedagogy - Szwabowski, Oskar (Hybris, 2014)
In the article I am analyzing the issue of a paradigm. My analysis is referring to pedagogy as a discipline in which the interpretation of the analyzed concept is still a matter of significant disagreement. A paradigm is still one of the key concepts which create the scholar identity of pedagogy. I point out the attempts of solving the difficulty of science which is the result of radical understanding of paradigm and I criticize them. At the end I outline the possibility of a different perception of the issue of the “paradigmatic of pedagogy”.